Antiplatelet Therapy, Platelet Function Testing, and Bleeding Complications in Cardiac Surgery Patients - Hansson, Emma C.; Jeppsson, Anders (Seminars in Thrombosis and Hemostasis, 2017)
Antiplatelet therapy with acetylsalicylic acid, alone or in combination with a P2Y12 inhibitor, reduces thromboembolic events in patients with coronary artery disease but increases the risk for spontaneous and perioperative bleeding complications. Both the antiplatelet effect and the risk for bleeding complications are larger with the new generation P2Y12 inhibitors prasugrel and ticagrelor than with clopidogrel. In this review, the perioperative handling of acetylsalicylic acid and the P2Y12 inhibitors clopidogrel, prasugrel, and ticagrelor will be discussed. In addition, the concept of platelet function testing in the surgical setting will be covered.
Keywords: antiplatelet therapy; acetylsalicylic acid; P2Y12 inhibitors; bleeding; coronary artery bypass grafting; platelet function testing